2019
DOI: 10.1088/0256-307x/36/5/057402
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and Fermi Surface Anisotropy in Transition Metal Dichalcogenide NbTe 2

Abstract: Transition metal dichalcogenides, featuring layered structures, have aroused enormous interest as a platform for novel physical phenomena and a wide range of potential applications. Among them, special interest has been placed upon WTe2 and MoTe2, which exhibit non-trivial topology both in single layer and bulk as well as pressure induced or enhanced superconductivity. We study another distorted 1T material NbTe2 through systematic electrical transport measurements. Intrinsic superconductivity with onset trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Often used for SdH oscillation analysis is a simplified version of the standard Lifshitz-Kosevich (LK) formula [45,47]: Angular-dependent magnetoresistance [48] or magnetic oscillation is a powerful tool to study FS anisotropy. An offset plot of FFT of oscillations at different Ξ (SM [31] Fig.…”
Section: B Magnetoresistance and Magnetic Oscillations In Tatementioning
confidence: 99%
See 1 more Smart Citation
“…Often used for SdH oscillation analysis is a simplified version of the standard Lifshitz-Kosevich (LK) formula [45,47]: Angular-dependent magnetoresistance [48] or magnetic oscillation is a powerful tool to study FS anisotropy. An offset plot of FFT of oscillations at different Ξ (SM [31] Fig.…”
Section: B Magnetoresistance and Magnetic Oscillations In Tatementioning
confidence: 99%
“…Angular-dependent magnetoresistance [48] or magnetic oscillation is a powerful tool to study FS anisotropy. Offset plot of FFT of oscillations at different 𝜃 (SM [31] Fig.…”
Section: B Magnetoresistance and Magnetic Oscillations In Tate4mentioning
confidence: 99%
“…Zhang et al reported the collapse of superconductivity when applied a pressure of 1.3 GPa on NbTe 2 . 21 Vaidya et al measured the electrical resistivity under pressure and found no abnormal change. 23 In addition, little is known about the properties of isostructural 1T″-TaTe 2 under pressure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, applying external pressure could achieved the bulk superconductivity of TaTe 2 between 4-6 K in the pressure range of 21-50 GPa 22 . As for isostructural CDW compound 1T'-NbTe 2 with 3×1 superstructure at 300 K 23 , such a LT phase has not been observed but exhibits superconductivity at T c ∌ 0.5 K 24 . Another analogue layered compound IrTe 2 with a 5d heavy transition metal element and strong Te-Te interlayer interaction shows a structural phase transition and transport properties anomaly as well 25 .…”
Section: Introductionmentioning
confidence: 98%